DESIGN OF A GEOSPATIAL DATABASE FOR DEPOSIT OF SOLID MINERALS (Journal of Geography and Environmental Management, 2025)
This article describes the features of designing a geospatial database structure for storing and managing results in solid mineral deposits.  Designing a geospatial database for solid mineral deposits requires a comprehensive approach, including the integration of multi-format data, ensuring topological integrity and compliance with modern standards. Technological problems of information storage and management in a GIS-oriented environment are considered. Implementation of structured database on the basis of ArcGIS Pro software,. ways of solution of data unification of different types of surveys, including relational databases, are highlighted.
Keywords: geodatabase; engineering-geological information; geoinformation systems; mineral deposit; data interpretation; data storage; relational queries; metadata